THE EFFECT OF EMOTIONAL INTELLIGENCE ON STUDENT SELF REGULATED LEARNING - LiLi Dianah; Oktariza, Sela (Institut Pendidikan Indonesia, 2024)
This study aims to examine the effect of emotional intelligence on the self-regulated learning of junior high school students in the West Bandung area. The approach used is a correlational quantitative approach, which allows measuring the strength of the relationship between these variables. The data collection technique used was a survey. Data were collected through questionnaires distributed directly to each junior high school in the West Bandung area. A total of 400 junior high school students were respondents in this study, selected using proportional stratified random sampling. The results showed that emotional intelligence has a positive and significant effect on self-regulated learning. The magnitude of the effect of emotional intelligence on self-regulated learning is 28.6%, with the remaining effect e attributed to other factors. The highest achievement indicator of emotional intelligence was that students always prayed in any situation, while the lowest achievement indicator was having a sense of empathy. The highest achievement indicator of self-regulated learning was setting learning goals, while the lowest was using learning resources. The higher the emotional intelligence, the higher the students' self-regulated learning.